Spatiotemporal expression and molecular characterisation of miR-344b and miR-344c in developing mouse brain - Leong, Angeline Jia Wen (2015)
Mammalian brain development requires a meticulous spatiotemporal regulation of gene and protein expression. The developing brain undergoes major construction during the embryonic stage, beginning with the formation of the neural tube that eventually gives rise to a complex nervous system. Studies had shown that microRNAs (miRNAs) played crucial roles in spatiotemporal regulation of the brain development. MiRNAs are small non-coding RNAs of about 22 nucleotides that regulate gene expression through inhibition or repression processes during post-transcriptional or translational stages. A recent study suggested that miR-344 was neural specific during brain development. In this study, we characterised the expression of miR-344b and miR-344c during the development of mouse brain. Bioinformatics analysis was employed to identify the potential downstream target genes of miR344b and miR-344c. Initially, miR-344b and miR-344c were found to target a total of 1,540 and 863 genes respectively. Genes that are known to be identified by three independent bioinformatics tools and also associated with transcription regulation and nervous system development were selected for further screening. The genes that fulfilled these criteria and targeted by miR344b and miR-344c were Olig2 and Otx2 respectively. Luciferase assay was performed to validate the target genes prediction. Overexpression plasmid was cotransfected with a 3’UTR plasmid and checked for luciferase protein inhibition. However, both Olig2 and Otx2 were not suppressed by their respective miRNAs. It may suggest that both Olig2 and Otx2 were not the direct targets of miR-344b and miR-344c or a more complex mechanism is involved. Parallel to bioinformatics study, in situ hybridisation analysis study showed that both miR- 344b and miR-344c were strongly expressed in the germinal layer during the early developmental stages of mouse brain. MiR-344b was not expressed in the brain from early postnatal until mature adult stage. Interestingly, miR-344c remained expressed throughout the P1 brain and its expression was still detectable in the mature adult brain although restricted to the olfactory bulb only. Higher magnification on the expression of miR-344b and miR-344c revealed that they were expressed in the nucleus. Stemloop RT-qPCR was employed to further investigate the expression level of these miRNAs in the brain and other multiple organs. The expression of miR-344b in the developing brain was peaked at E15.5 and decreased steadily as it progressed to adulthood. On the other hand, miR-344c showed high expression at E15.5 and remained steady till the adult stage. Both miR-344b and miR-344c showed highest expression in adult pancreas when comparing with the adult multiple organs, in line with the previous study reported that miR-344 was highly expressed in the pancreas. In conclusion, Olig2 and Otx2 were not direct targets of miR-344b and miR-344c respectively as previously predicted. However, this study proves that miR-344b and miR-344c were expressed in the developing mouse brain, especially localised to the nucleus of the neuronal cells. In addition to whole brain, miR-344b and miR-344c were highly expressed in pancreas and lowly expressed in muscles.